Quantitative assessment of provisions for the right to access to education of persons with disabilities (2015)
The quantitative method was applied in gleaning information on the type and degree of legal provisions on the rights of access to education of persons with disabilities (PWDs) in Nigeria. Using the six Geo-political zones of Nigeria, the paper reasoned that participants’ perception and or opinions on rights of access to education, its acceptability, availability and affordability is not discriminatory irrespective of whether the beneficiaries are people with disabilities and or (otherwise, without disabilities). The study utilized the descriptive survey research design subsumed within the ex-post-facto method while it drew and used, through a simple random sampling technique, 399 participants from among tertiary institutions’ students, teachers and administrators who voluntarily completed a Self-constructed and validated research measure tagged ‘the Rights of Persons with Disabilities to Education Inventory’ (RoPDEI). Multiple regression statistical methods at 0.05 alpha was applied. While the findings showed that the provision of rights to education for PWDs (p<0.05) and expected reforms to equal access (p<0.05) were statistically significant. Of the clustered variables however, only “sympathy/pity” and “empathy” accounted for approximately 25% (p<0.05) and 18% (p<0.05) contribution respectively. Furthermore, the disability-type (p>0.05) was not significant; even though, in considering the factor contribution, participants who submitted that “they were people without disabilities” had beta weight of 23.5% (approximately 24%) (p<0.01) to the variance. It thus recommended inter-alia, that the Federal Government of Nigeria should legislate specifically on the rights of PWDs in keeping with its obligation under the United Nations Convention on the Rights of Persons with Disabilities (CRPD); and that the enactment of an Act to domesticate the convention on the Rights of PWDs in Nigeria should be urgently put in place. All socio-environmental and funding barriers to legislative reforms should be mitigated.